Unethical Recruitment Practices and Whistleblowing - Belghit, Anne Goujon; Husser, Jocelyn; Lacaze, Delphine; Sahut, Jean-Michel (Group & organization management, 2025)
This study uses a sample of French professionals in human resource management (HRM) to examine the influence of the perceived violation of the psychological contract, moral potency, and ethical decision-making (EDM) on an individual’s intention to blow the whistle when observing unethical recruitment practices. The dilemmas presented to the study respondents reproduced six original HRM scenarios. The findings revealed that moral potency and the EDM process were positively associated with whistleblowing for the six scenarios. The perception of violating the psychological contract was also positively linked to the whistleblowing intention in a magnitude of consequences and a social consensus approach. Finally, the study reveals that a person’s knowledge of their company’s whistleblowing policy does not influence their intention to blow the whistle, except for three factors: social consensus, probability of effect and temporality. HR professionals are neither heroes nor enemies of their organizations, but they may be willing to blow the whistle because they are well-versed in the internal systems of their companies such as the social contract to the system codes.